Pharmacokinetic Evaluation of Natural Resin Coated Microcapsules of Nifedipine - CHOWDARY, K.P.R.; MOHAPATRA, PRITHWIRAJ; MURALI KRISHNA, M.N. (Asian Journal of Chemistry, 2010)
Resin coated microcapsules of nifedipine were prepared by emulsification- solvent evaporation method employing (i) olibanum resin and (ii) colophony as coat materials and were subjected to pharmacokinetic evaluation with an objective to evaluate their release retarding and rate controlling efficiency in vivo. Nifedipine release from the resin coated microcapsules was slow and spread over 24 h. In the in vivo study, the rapid absorption of nifedipine with a rate constant (Ka) of 4.51 h-1 was observed following the oral administration of nifedipine soft capsules. The absorption of nifedipine was slow over longer periods of time with a rate constant (Ka) of 0.124 and 0.134 h-1 with olibanum and colophony coated microcapsules, respectively. The mean residence time (MRT) was found to be increased from 3.43 h for soft capsule to 10.9 h and 10.25 h, respectively with olibanum and colophony coated microcapsules indicating longer stay of the drug in the body when it was administered as resin coated microcapsules. The relative bioavailability of olibanum and colophony coated microcapsules was 126.75 and 113 %, respectively when compared to soft capsules (100 %).